Calculation of temperature distribution and rheological properties of the lithosphere along transect I in the Western Carpathians - DÉREROVÁ, Jana; KOHÚT, Igor; BIELIK, Miroslav; BOŠANSKÝ, Marián; PORUBČANOVÁ, Barbara (Contributions to Geophysics and Geodesy, 2012)
Using the 2D integrated modelling method, we calculated the temperature model of the lithosphere along transect I passing through theWestern Carpathians. Based on the extrapolation of failure criteria, lithology and calculated temperature distribution, we derived the rheology model of the lithosphere in the area. Our results indicate clearly that the strength decreases from the Bohemian Massif via the Western Carpathians to the Pannonian Basin. The largest strength can be observed within the upper crust on the boundary between the upper and lower crust. This phenomenon is typical for all studied tectonic units: the Bohemian Massif, the Western Carpathians and the Pannonian Basin. These results suggest mostly rigid deformation in the upper crust of the units. By contrast, the lower crust in the Bohemian Massif and the Western Carpathians reflects significantly lower strength, while in the Pannonian Basin the strength is the smallest. In all tectonic units the strength within the uppermost mantle (lower lithosphere) disappears. It can be suggested that the ductile deformation dominates in this part of the lithosphere.